Bidirectional Step-Up/Step-Down DC-DC Converter with Magnetically Coupled Coils - Frivaldsky, Michal; Dobrucky, Branislav; Scelba, Giacomo; Spanik, Pavol; Drgona, Peter (Communications - Scientific letters of the University of Zilina, 2013)
The paper is focused on bidirectional up/down DC-DC converter with magnetically coupled coils (MCC), which can be utilized as a part of power semiconductor system in traction, automotive, or industrial applications like renewable energy sources. Proposed solution of main circuit of bidirectional converter should serve for energy transfer from source to load, and vice versa, whereby parameters of electrical variables like voltage, current and power are able to be adapted based on the current requirements of application. Their values can be increased or decreased in first (energy transfer from source to load) or in third (energy transfer from load to source) quadrant of converter’s operation. The boost effect of output voltage can be increased - if it is not sufficient one - by appropriate ratio of number of inductor windings.